The impact of public expenditures on economic growth of the Republic of North Macedonia - Nikoloski, Aleksandar (Technium Social Sciences Journal, 2020)
Ensuring high and sustainable economic growth is one of the main tasks of public spending policy. In fact, public expenditure plays an important role in the formation of physical and human capital over time. If are properly targeted, they can stimulate economic growth even in the short term, when limited infrastructure of (unskilled) workforce is a barrier to increased production. Therefore, the realized impact of public expenditures on economic growth can be considered as an indicator of their effectiveness. The goal of public expenditure is to increase economic growth by providing more employment opportunities, increasing people's income and living standards. Therefore, if they are well-managed, they can lead to the desired level of economic growth and improvement of the living standard of the population.